Richard Rorty’s Sentimentalist Approach to Human Rights - Seyed Masoud Moosavi Karimi; Mehdi Delgir (حقوق بشر)
Understanding human nature, and the rights and duties resulting from it, has long been a concern for philosophers. After World War II, this led to the foundation of the movement known as the human rights movement with the adoption of the Universal declaration of Human Rights. Richard Rorty opposes all foundationalist schools, to which the human rights movement mainly belonged, referring to them as being inefficient in respecting human rights. Rorty believes that promoting and explaining the sentimentalist approach is the best way to promote and defend human rights. According to sentimentalist approach, the difference between human beings and animals does not just lie in the fact that the former possesses a unique intellectual capacity, but in the fact that human beings enjoy a wide range of emotions and feelings. Rorty believes that we are able to defend human rights by taking advantage of sentimental education, and promoting empathy. This article explores the philosophical foundations of Rorty’s approach to human rights. Starting by a review of Rorty’s critiques of the competing philosophical readings of human rights, the article sums up other’s criticisms of Rorty’s own view. And by proposing answers to those critiques, it suggests that Rorty’s explanation of human rights in a pragmatic framework is both philosophically viable, and practically efficient.